A comunidade de Pimplinae (Hymenoptera, Ichneumonidae) em área de Mata Atlântica de região de Campos do Jordão, SP, Brasil : taxonomia, diversidade e distribuição - Loffredo, Ana Paula da Silva (2008)
The present work had for aim to survey of Pimplinae fauna in area of Atlantic forest at Campos do Jordão, SP, contributing to the taxonomic knowledge of the group as well to investigate the occurence of possible pattern of spatialdistribution of those insects, considering a altitudinal gradient (600- 2000m) and the seasonal influence that the study area is submitted. Using Malaise traps and "sweeping" the vegetation in 15 points in different altitudes were obtained 546 identified specimens distributed in 16 genera and 65 morphospecies. Schyzopyga Gravenhorst, 1829 was mentioned for the first time to Brazil. For the genera Hymenoepimecis Viereck, 1912 and Zaglyptus Foerster, 1869 three and two new species were described respectively. The species of Pimpla Fabricius, 1804 and Neotheronia Krieger, 1899 were the most frequent. It was not possible to observe a distribution pattern according to the gradient altitudinal for the community of Pimplinae. The results obtained in this study enlarge the knowledge regarding the distribution of Pimplinae in neotropical region, and contribute to studies about distribution of parasitoid insects along an altitudinal gradient